Contributing Factors to Customer Satisfaction during the Pandemic: A Study of Foodpanda of Malaysia and Nigeria - Kee, Daisy Mui Hung; Veeraselvam, Vinosha Rai A/P; Vayapuri, Vanishaa A/P; Aisyah, Ummie; A'ishah, Tuan Amelin; Enakhifo, Ernestina; Edeh, Friday Ogbu (AIBPM Publisher, 2022)
The study on Foodpanda, an online food and grocery service app, examines the contributing factors leading to customer satisfaction during the global pandemic. As the new norms such as social distancing increased the demand for food delivery, The study examines the relationship between service quality, product information quality, the convenience of use, and customer satisfaction. A total of 102 Foodpanda users completed the online survey questionnaires. The findings revealed that convenience of use and product information quality hold the highest percentage in the contribution to customer satisfaction. The implication and recommendations are presented.Â